The causes of stress at work amongst social workers - Raudeliunaite Rita; Volff Giedre (SHS Web of Conferences, 2020)
Social workers work in an ever-changing social, political and cultural environment, they are exposed to contacts with persons of different social backgrounds, people experiencing behavioural and various social problems. In complicated, ever-continuing, multidimensional situations, there arises the risk of stress. In order to manage stress at work, it is important to identify the causes of stress. The objective of this study is to reveal the causes of stress experienced by social workers at work basing on the experience of social workers. Qualitative research type was chosen for the study. The method of a semi-structured interview with social workers, who work in different institutions providing social services, was used. The study revealed both external and internal causes posing stress to social workers at work. The external causes of stress are associated with working conditions, for example, the absence of stability and clarity at work. Social workers often remain alone to resolve problems; they can have a heavy workload. There is the lack of cooperation between institutions, such as the police and other institutions when they inform about the problematic behaviour of their client. Stress is caused by the absence of change and excessively high requirements for an employee. Social workers experience negative behaviour of service receivers, for example, threat of physical violence, psychological violence, and pressure from clients in order to receive something. Relationships with management can also cause stress. There is the lack of incentive, the lack of benevolence, an employee is noticed only when he needs “to be taught a lesson”; the conditions of employment are not satisfactory – an employee is offered only a fixed-term contract, low pay. The internal causes of stress are related to excessively high requirements for social workers, the pursuit of perfection when resolving the problems of service receivers, the fear of failure and an inflated sense of responsibility.